Dynamic autoregulatory response after aneurysmal subarachnoid hemorrhage and its relation to angiographic vasospasm and clinical outcome - Fontana, Johann; Ehrlich, Gregory Marius; Scharf, Johann; Weiß, Christel (Neurocritical care, 2015)
BackgroundImpaired cerebral autoregulation (CA) is increasingly recognized to contribute to sequelae after aneurysmal subarachnoid hemorrhage (SAH). The current study characterizes the course of the dynamic autoregulation index (ARI) during the first 8 days after SAH and its coherence with angiographic vasospasm (VS) and clinical outcome.MethodsFifty-one patients with SAH were prospectively included within 48 h after the ictus. The ARI was determined daily for each hemisphere with the thigh cuff test. The degree of cerebral VS was evaluated based on a baseline digital subtraction angiography (DSA) after the ictus and a follow-up DSA on day 8. The clinical outcome was determined by the Modified Rankin Scale (mRS), the Glasgow Outcome Scale Extended (GOSE), and the National Institute of Health Stroke Scale (NIHSS) at discharge from the intensive care unit.ResultsImpaired CA significantly correlated with unfavorable clinical outcome scores (mRS, p = 0.0021; GOSE, p = 0.0027; NIHSS, p = 0.0091). ARI-values of patients with a favorable clinical outcome (mRS 0-3) showed a significant improvement during the first 8 days (+0.1964/day; p = 0.0148) compared to a significant decrease of ARI-values in patients with an unfavorable clinical outcome (-0.2976/day; p = 0.0182). The degree of CA impairment significantly correlated with the severity of VS in the middle cerebral artery (p = 0.0184).ConclusionsEarly deterioration of CA significantly correlates with unfavorable clinical outcome and severity of angiographic vasospasm. Dynamic CA measurements might represent an important tool in stratifying therapy guidelines in patients after SAH.
Gesehen am 07.09.2017